2021
DOI: 10.3390/cancers13133140
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics for Discovery of Early Metabolic Markers of Prostate Cancer Based on Ultra-High-Performance Liquid Chromatography-High Resolution Mass Spectrometry

Abstract: Background: The prevention and early screening of PCa is highly dependent on the identification of new biomarkers. In this study, we investigated whether plasma metabolic profiles from healthy males provide novel early biomarkers associated with future risk of PCa. Methods: Using the Supplémentation en Vitamines et Minéraux Antioxydants (SU.VI.MAX) cohort, we identified plasma samples collected from 146 PCa cases up to 13 years prior to diagnosis and 272 matched controls. Plasma metabolic profiles were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…In this study, the expression levels of 2-hydroxyadenine, thymine, and 8-hydroxyguanine were downregulated after brain injury, suggesting that nucleotide metabolism balance was related to the occurrence of cerebral ischemia. In addition, the tricarboxylic acid cycle (TCA) is a common metabolic pathway for carbohydrate, fat, and protein metabolism, and 2-hydroxyadenine served as fuel for the TCA, which suggested that the occurrence of IS was related to TCA [ 27 ]. Studies have shown that after brain injury, the expressions of citric acid, fumaric acid, and malic acid were decreased, indicating that the TCA pathway was inhibited [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression levels of 2-hydroxyadenine, thymine, and 8-hydroxyguanine were downregulated after brain injury, suggesting that nucleotide metabolism balance was related to the occurrence of cerebral ischemia. In addition, the tricarboxylic acid cycle (TCA) is a common metabolic pathway for carbohydrate, fat, and protein metabolism, and 2-hydroxyadenine served as fuel for the TCA, which suggested that the occurrence of IS was related to TCA [ 27 ]. Studies have shown that after brain injury, the expressions of citric acid, fumaric acid, and malic acid were decreased, indicating that the TCA pathway was inhibited [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Our previous study nested within the NSHDS 10 and the three EPIC studies 9,11,12 employed a targeted methodology, a kit-based LC-MS 2 assay (Biocrates, Innsbruck, Austria). The three ATBC studies, [5][6][7] one of the SU.VI.MAX studies, 14 the PLCO study, 8 and Cancer Prevention Study-II Nutrition study 16 employed an untargeted MS platform and included only identified metabolites prior to statistical analysis. No previous study employed the (untargeted) analytical methodology used in the present study, that is, LC-high-resolution MS with untargeted data processing using XCMS prior to the feature identification.…”
Section: Other Studiesmentioning
confidence: 99%
“…Eleven other prospective studies (six different cohorts) investigating the association of metabolite levels with PCa risk have been published (referred to as “the 11 studies” hereafter) 5‐14,16 . These studies differed in their experimental design and analytical methodologies.…”
Section: Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites (≤1.5 kD), which include sugars, fatty acids, amino acids, nucleotides, alkaloids, and steroids [1,8] can sometimes be enzymatically transformed into epimetabolites, allowing them to regulate physiological processes [9][10][11]. Because biological matrices are complex with thousands of metabolites in them, the use of analytical methods such as metabolomics allows individual metabolite measurements to be managed [12][13][14][15][16][17][18]. The difference between the two types of metabolomics is that the untargeted approach identifies a single metabolite in a hypothesis-driven manner, while the targeted approach quantifies a metabolite of interest a priori [1,2,19].…”
Section: Introductionmentioning
confidence: 99%